Nursing students’ work readiness and its influencing factors before participating in a nurse residency program: a multicenter cross-sectional study - Chen, Liping; Lin, Qin; Xu, Ye; Wu, Liping (Frontiers in Medicine, 2024)
Background: Studies have shown that work readiness is closely related to nurses' role adaptation, career development, and patient safety. However, we know little about the nursing students' work readiness and its influencing factors before participating in a nurse residency program, and whether factors have changed from before. Aim: (1) To investigate the work readiness of nursing students ready to engage in a nurse residency program; (2) to identify the factors affecting the nursing students' work readiness and the associations between emotional intelligence and work readiness; and (3) to discuss the changes of factors affecting nursing students' work readiness. Design: An online, multicenter cross-sectional study. Methods: 878 nursing students from eight tertiary hospitals in Chongqing, China were recruited. The online investigation used the General Information Questionnaire, the Nursing Students' Work Readiness Scale, and the Emotional Intelligence scale. The data were analyzed using IBM SPSS V23.0. Results: 768 valid questionnaires were included in this study. The nurses obtained a work readiness score of 277.08 ± 44.39 and an emotional intelligence score of 89.57 ± 13.89. Univariate analysis revealed that the following factors affected work readiness: age, sex, family support for becoming a nurse, voluntary choice of nursing major, previous experience as a student cadre, scholarship recipient status, willingness to engage in nursing work during the COVID-19 pandemic and confidence in clinical nursing practice. Frequent incidents of violence, poor salary for nurses for the nurse residency program, and low social acceptance were the top three reasons for decreased confidence in clinical nursing among nursing students. Furthermore, multiple linear regression analysis indicated that age, voluntary choice of nursing major, student leadership experience, confidence in clinical nursing work, selfemotion, and emotional application significantly influenced nurses' work readiness. Conclusions: Clinical instructors and administrators should dynamically assess nurses' work readiness, prioritize individuals aged ≤ 23, who have chosen the nursing profession involuntarily, lack prior experience as student cadres, and exhibit low confidence in clinical nursing work. This focus will enhance their emotional self-management skills and ability to apply emotions effectively, improving their work readiness and training efficacy.